ULTRASOUND GUIDED AXILLARY LYMPH NODE BIOPSY IN BREAST CANCER PATIENTS - Fatima, Kulsoom (Journal of Ayub Medical College Abbottabad, 2019)
Dear Editor, I read with interest, the article in Journal of Ayub Medical College titled ’˜Diagnostic accuracy of US-FNAC of axillary lymph nodes in patients with primary breast cancer using Sentinel lymph node biopsy as standard reference.1 I agree with the authors that ultrasound guided needle biopsy is an effective way to triage patients with newly diagnosed breast cancer and suspected axillary lymph nodes, for deciding whether they need axillary lymph node dissection (ALND) or not. ALND has significant complications.2,3 At our institute the practice is to perform ultrasound guided core biopsy of the suspicious axillary lymph node rather than fine needle aspiration cytology (FNAC). We usually use 18-gauge needle for obtaining the cores. If the core biopsy turns out negative then the patient undergoes sentinel lymph node biopsy (SLNB) at the time of surgery for definitive evaluation of the axilla. This algorithm is also shown in the figure 3 of the above-mentioned article. I however do not understand why all the patients mentioned in the study underwent SLNB irrespective of the FNAC results. This is contrary to the worldwide practice where only patients with negative lymph nodes on ultrasound guided biopsy undergo SLNB.4,5 Patients with positive lymph nodes proceed directly to axillary lymph node dissection. Another point that needs to be clarified is what has been quoted in introduction as well as discussion section. The authors quote: According to one study, US guided FNAC was performed in 1,152 cases. Eight hundred and twenty-one patients had malignant lymph nodes which resulted in avoiding 11.7% of patients to undergo needless SLNB.’’ It is to be noted 821 out of 1152 does not equate to 11.7%. Also, the study that they quote actually mentions that positive FNAC results enabled 11.7 % of cN0 patients (373/3,175) to avoid unnecessary SLNB.5